2007
DOI: 10.1016/j.fsi.2006.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The immune response of tilapia Oreochromis mossambicus and its susceptibility to Streptococcus iniae under stress in low and high temperatures

Abstract: Mozambique tilapia Oreochromis mossambicus acclimated to 27 degrees C were then held at 19, 23, 27 (control), 31 and 35 degrees C, and were examined for non-specific cellular and humoral responses after 12-96 h. Total leucocyte count decreased significantly when fish were transferred to 19 and 23 degrees C after 48 and 96 h, and when transferred to 35 degrees C over 12-96 h, respectively. Respiratory burst decreased significantly when fish were transferred to 19, 31 and 35 degrees C over 24-96 h, whereas phago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(110 citation statements)
references
References 35 publications
6
101
1
2
Order By: Relevance
“…Cold-stress induces changes in serum levels of IgM, leukocyte count (WBC), phagocytosis, thyroxine (T 4 ) and catecholamines in tilapia . Transferring tilapia from 27°C to lower temperatures (19 and 23°C), or to higher temperatures (31 and 35°C), reduces their immune capability, and involve changes to WBC, lysozyme (LZM) and the phagocytic index (Ndong et al, 2007). Plasma LZM level is not correlated with sex, parental origin, rearing length, weight, condition factor or rearing density (Caruso and Lazard, 1999) but handling, transport and toxic water change the levels of LZM (Möck and Peters, 1990;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cold-stress induces changes in serum levels of IgM, leukocyte count (WBC), phagocytosis, thyroxine (T 4 ) and catecholamines in tilapia . Transferring tilapia from 27°C to lower temperatures (19 and 23°C), or to higher temperatures (31 and 35°C), reduces their immune capability, and involve changes to WBC, lysozyme (LZM) and the phagocytic index (Ndong et al, 2007). Plasma LZM level is not correlated with sex, parental origin, rearing length, weight, condition factor or rearing density (Caruso and Lazard, 1999) but handling, transport and toxic water change the levels of LZM (Möck and Peters, 1990;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In gilthead sea bream, Sparus aurata, lysozyme activity decreased significantly when transferred from 18°C to 11°C (Tort et al, 2004). Likewise, Ndong et al (2007) found that lysozyme activity decreased significantly when juvenile tilapia Oreochromis mossambicus were transferred from 27°C to 19°C after 12-96 h, but increased significantly when transferred to 31°C and 35°C over 48-96 h. Conversely, some studies have not found an effect of water temperature on serum lysozyme levels (Olsen et al, 1993). Interestingly, plasma lysozyme activity was significantly lower at 25°C than that at 20°C or 35°C in the current study, suggesting that the fish were under less thermal stress.…”
Section: Discussionmentioning
confidence: 98%
“…Ainsworth et al (1991) found that phagocyte function was significantly suppressed in channel catfish, Ictalurus punctatus, acclimatized at 10°C, but unchanged at 18°C. Ndong et al (2007) reported that both phagocytic activity and the phagocytic index decreased after 12 and 24 h in tilapia, O. mossambicus, that were transferred from 27°C to low temperatures (19°C and 23°C). However, levels returned to normal after 48 h, suggesting that the fish had the ability to adapt to temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…Tetapi pada saat-saat tertentu, nafsu makan ikan menurun. Hal ini diduga terjadi karena diakibatkan fluktuasi suhu harian yang menyebabkan ikan stress sehingga menurunkan nafsu makan (Ndong et al, 2007).…”
Section: Pembahasanunclassified